Relation of Financial Literacy with Financial Attitude and Financial Behavior among Tharu Woman Small Borrowers - Rashesh Vaidya; Ramseh G.C. (Profesional Muda Cendekia Publishing, 2021)
Tharu are an ethnic group indigenous to the Terai region of Nepal stretching from east to west low-land of Nepal. The Tharu communities are normally residing in most of the districts of the Terai belt of Nepal. The paper tries to find out the relationship between financial literacy with financial attitude and financial behavior among the Tharu community women of Nepal. Hence, the paper has conducted a survey among the Tharu women living at Nawlapur District of Gandaki Province of Nepal. The paper found that Tharu women who are in a saving group, mainly focused on income saving and looking for an opportunity cost. Similarly, Tharu women associated with a saving group, are mainly concerned with the utilization of the credit, they had taken and worked for the repayment of the credit in time. The study also found that financial literacy has highly influenced financial behavior among Tharu women of Nepal. At the same time, the level of financial literacy is not seen as highly influencing the financial attitude among the Tharu women of Nepal.